PENERAPAN PERMAINAN ANSAMBEL PIANIKA UNTUK STIMULASI MINAT BELAJAR MUSIK SISWA KELAS V SDN 2 BOJONGMENGGER - Deden Gandara; Resa Respati (STKIP Subang, 2026)
The background of this research is the low interest in learning music of fifth-grade students at SDN 2 Bojongmengger, indicated by a lack of attention and active participation in the learning process. This study aims to determine the implementation of melodica ensemble playing and to describe the stimulation of students' interest in learning music after the application of the method. The research method used is quantitative with a Pre-Experimental design in the form of a One-Shot Case Study. The research sample used a saturated sampling technique involving all 11 fifth-grade students at SDN 2 Bojongmengger. Data were collected using a closed 1-5 Likert scale questionnaire that had been tested for validity and reliability (26 valid items), then analyzed using descriptive statistics based on Azwar's three-level criteria. The results showed that the implementation of melodica ensemble playing for four meetings was carried out very well through structured stages. Post-intervention, students' overall interest in learning music was in the high category with a total average score of 105.37. Specifically, 63.6% of students achieved high criteria and 36.4% were in medium criteria. Thus, the application of melodica ensemble playing proved effective as a stimulation medium to increase students' interest in learning music in elementary schools.